PENGARUH INTERAKSI, KEHADIRAN PENGAJAR DAN KEHADIRAN SOSIAL TERHADAP KEPUASAN PEMBELAJARAN ONLINE PADA MATA PELAJARAN EKONOMI DI SMA NEGERI 13 SURABAYA PADA MASA COVID-19 - Nabila Devi Indah Sari; Riza Yonisa Kurniawan (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractOnline learning satisfaction in students is the most important thing in determining a successful learning, learning satisfaction can be influenced by interaction, the presence of teachers, and social presence. Good online learning will support student learning satisfaction. The purpose of this study was to analyze whether there was an effect of interaction, teacher presence and social presence on online learning satisfaction in economic subjects at SMA Negeri 13 Surabaya during the Covid-19 period. The research subjects in this study were class X and XI IPS SMA Negeri 13 Surabaya which contained economic subjects with a total of 271 students. Data were collected using an instrument in the form of a questionnaire. The data analysis in this study used Structural Equation Modeling (SEM) using the WarpPLS version 7.0 software. The results of this study indicate that (1) The interaction has a significant effect on online learning satisfaction. (2) The interaction has a significant effect on social presence, (3) The presence of the teacher has no effect on online learning satisfaction (4) the presence of the teacher has a significant effect on social presence and (5) Social presence has a significant effect on online learning satisfaction. (6) significant interaction has an indirect effect on online learning satisfaction through social presence. (7) The presence of the teacher indirectly has no significant effect on online learning satisfaction through social presence.Keywords: Interaction, Teacher Attendance, Social Presence, and Online Learning Satisfaction